Charismatic Leadership Kh. Zezen Zainal Abidin Bazul Asyhab In Education of Iqomah Nusantara - Nandang Koswara; Deti Rostini; Aang Abdullah Zein; Iis Farida Zein; Dian Anggaraeni (Pascasarjana Pendidikan Agama Islam Institut KH. Abdul Chalim Mojokerto, 2022)
Research on charismatic leadership KH. Zezen Zainal Abidin Bazul Asyhab in building the Qoryah Mubarokah Association (IQOMAH) association is a research related to the ability of leaders to influence others towards a better and life. Based on the data obtained, the focus of the Iqomah program is the enforcement of Islamic law in the field of Worship, named as the practice of the Islamic Pillars correctly and earnestly. The research includes the type of field research (field research) with qualitative methods. Based on this method, facts were found in the field, using observational data collection techniques, interviews and documentation of Iqomah's programs and policies. The first conclusion is that charismatic leadership is the ability of leaders to influence members in particular and society in general to achieve the vision and mission of a leader. Second, based on the study’s results, there are characteristics and indicators of charitable leadership in the figure of KH. Zezen Zainal Abidin Bazul Asyhab. Third, the continuity and consistency of educational programs at Iqomah Nusantara as proof of the influence of KH. Zezen Zainal Abidin Bazul Asyhab is a charismatic leader, even though he has passed away.